2017
DOI: 10.1007/s13197-017-2769-3
|View full text |Cite
|
Sign up to set email alerts
|

Jabuticaba (Myrciaria jaboticaba) juice obtained by steam-extraction: phenolic compound profile, antioxidant capacity, microbiological stability, and sensory acceptability

Abstract: Jabuticaba () is a dark-colored fruit native to Brazil that has a desirable flavor and high anthocyanin content. In the present study, jabuticaba juice was produced by steam-extraction and the phenolic compound profile, antioxidant capacity, instrumental color, and microbiological quality were evaluated during 90 days of storage at 25 °C. Cyanidin-3--glucoside represented 45% of the total phenolic content of the juice, which reduced with extent of 80% during storage. Total phenolic content of the juice increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
1
13
2
Order By: Relevance
“…However, due to the low analytical error of these physicochemical determinations, small variations in absolute values become statistically significant, which, in practical terms, will not cause relevant physicochemical changes at industrial level. Slight or no variations in physicochemical parameters of stored fruit drinks were also observed by Onada et al (2018) and Figure 2. pH (A), soluble solids (B) and titrable acidity (TA) (C) of juçara, banana and strawberry smoothie during storage at 7 °C and 25 °C.…”
Section: Bioactive Compoundsmentioning
confidence: 64%
See 1 more Smart Citation
“…However, due to the low analytical error of these physicochemical determinations, small variations in absolute values become statistically significant, which, in practical terms, will not cause relevant physicochemical changes at industrial level. Slight or no variations in physicochemical parameters of stored fruit drinks were also observed by Onada et al (2018) and Figure 2. pH (A), soluble solids (B) and titrable acidity (TA) (C) of juçara, banana and strawberry smoothie during storage at 7 °C and 25 °C.…”
Section: Bioactive Compoundsmentioning
confidence: 64%
“…As antioxidant capacity did not vary, it is suggested that the thermal degradation of anthocyanins may lead to the formation of other phenolic compounds of equal or even higher antioxidant potential (Patras et al, 2010). Onada et al (2018) verified the increase in total phenolic compounds and antioxidant capacity of jabuticaba juice obtained by steam extraction and stored at room temperature for 90 days, in spite of the degradation of anthocyanins such as cyanidin and delphinidin. Since the authors determined the phenolic compounds profile of the product during storage, they suggested that the depolymerization of ellagitannins to ellagic acid and the cleavage of anthocyanins, which degradation product is gallic acid, were the responsible phenomena for this behavior, since the concentration of ellagic and gallic acids increased significantly throughout the study.…”
Section: Bioactive Compoundsmentioning
confidence: 78%
“…At higher storage temperatures, anthocyanins degradation was even faster (e.g., total loss after 14 days at 60 °C). Extensive losses have also been reported in berries juices [ 3 , 4 , 11 ]. Although gallic acid content did not change after 112 days at 25 °C, it increased (from 38% to 226%) when juice was stored at higher temperatures ( Figure 2 C).…”
Section: Resultsmentioning
confidence: 99%
“…Extraction times superior to 30 min led to less expressive increases in both yield and anthocyanin content while resulted in more noticeable aftertaste. The amount of added sucrose (6% w/v ) was based on previous literature data [ 3 ]. SJJ was produced to evaluate the impact of sucrose addition on jaboticaba juice processing and on its phenolic compounds stability during storage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation